Glial cells: an important switch for the vascular function of the central nervous system - Gao, Ling; Pan, Xuezhen; Zhang, John H.; Xia, Ying (Frontiers in Cellular Neuroscience, 2023)
In this review, we first describe the current understanding of glia-mediated vascular function affecting the role of blood-brain barrier (BBB) in central nervous system (CNS) disorder. BBB, mainly composed of glia and endothelial cells (ECs), is the protective structure that orchestrates the transport of substances, including ions, molecules and cells, from brain vessels into or out of CNS. Then, we display the multiple communication between glia and vascular function based on angiogenesis, vascular wrapping and blood perfusion in brain. Glia can support microvascular ECs to form a blood network connecting to neurons. Astrocyte, microglia and oligodendrocyte are the common types of glia surrounding the brain vessel. Glia-vessel interaction is required for the permeability and integrity of BBB. Glial cells surrounding cerebral blood vessels can transmit communication signals to ECs and regulate the activity of VEGF- or Wnt-dependent endothelial angiogenesis mechanism. In addition, these glia cells monitor the blood flow in the brain via Ca2+/K+-dependent pathways. Finally, we provide a potential research direction of glia-vessel axis in CNS disorder. Microglial activation can trigger astrocyte activation, which suggesting microglia-astrocyte interaction may be the key role in monitoring cerebral blood flow. Thus, microglia-astrocyte interaction can be the key point of follow-up studies focusing on microglia-blood mechanism. More investigations focus on the mechanism how oligodendrocyte progenitor cells communicate and interact with ECs. The direct role of oligodendrocytes in modulating vascular function needs to be explored in the future.